STRATEGI PEMBELAJARAN BERBASIS MASALAH - Zafira, Alya Zahra; Dieni, Hafizah; Gusmaneli, Gusmaneli (Sindoro: Cendikia Pendidikan, 2025)
Abstract This research aims to improve student’s ability to solve problems in the learning process. This study discusses a problem-based learning strategy that places students as the center of learning with a focus on solving real problems. This strategy encourages students to learn independently, discuss, and think critically in finding solutions to problems relevant to everyday life. Through this strategy, students not only gain knowledge, but also develop problem-solving skills and have independent learning abilities that are important for facing challenges in the learning process. Data collection was carried out through literature studies from textbooks, scientific journals, articles, and other publications. The results show that the application of problem-based learning strategies is effective in improving students' ability to solve problems in the learning process. Keywords: Learning Strategy, Problems, Learning. Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan peserta didik memecahkan masalah dalam proses pembelajaran. Penelitian ini membahas strategi pembelajaran berbasis masalah yang menempatkan peserta didik sebagai pusat pembelajaran dengan fokus pada penyelesaian masalah nyata. Strategi ini mendorong peserta didik untuk belajar secara mandiri, berdiskusi, dan berpikir kritis dalam mencari solusi terhadap permasalahan yang relevan dengan kehidupan sehari-hari. Melalui strategi ini, peserta didik tidak hanya memperoleh pengetahuan, tetapi juga mengembangkan keterampilan pemecahan masalah dan memiliki kemampuan belajar mandiri yang penting untuk menghadapi tantangan dalam proses pembelajaran. Pengumpulan data dilakukan melalui studi literatur dari sumber buku pelajaran, jurnal ilmiah, artikel, dan publikasi lainnya. Hasilnya menunjukkan penerapan strategi pembelajaran berbasis masalah efektif dalam meningkatkan kemampuan peserta didik dalam memecahkan masalah dalam proses pembelajaran. Kata kunci: Strategi Pembelajaran, Masalah, Belajar.